2020
DOI: 10.3390/ijerph17061964
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prehospital Care of Migrants Who Arrive Intermittently at the Coasts of Southern Spain

Abstract: Background: The aim of this study is to identify the sociodemographic characteristics and the most frequent diseases and nursing interventions carried out on migrants arriving by sea at southern Spain. Method: Cross-sectional, descriptive, and retrospective study based on the database of the Spanish Red Cross Intervention Activation System. All migrants who arrived on the coasts of a southern province during 2016 and were assisted by the Red Cross were included. Results: A total of 2027 people were registered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Another Spanish study on immigrants arriving by sea at southern Spain, during 2016, notices a higher prevalence of health issues on immigrants from Sub-Saharan Africa as compared to the ones from Maghreb countries, mainly attributed to the higher duration of their travel and thereby prolonged exposure of themselves to harsh conditions [12]. Cañardo et al [13], operating with the non-governmental organization (NGO) Open Arms, agree on the fact that the majority of the population up until 2018 originated from Sub-Saharan countries and that their health status appeared to be directly linked to the poor and precarious living conditions in transit [13].…”
Section: A the Patient Population In Distress At Seamentioning
confidence: 99%
“…Another Spanish study on immigrants arriving by sea at southern Spain, during 2016, notices a higher prevalence of health issues on immigrants from Sub-Saharan Africa as compared to the ones from Maghreb countries, mainly attributed to the higher duration of their travel and thereby prolonged exposure of themselves to harsh conditions [12]. Cañardo et al [13], operating with the non-governmental organization (NGO) Open Arms, agree on the fact that the majority of the population up until 2018 originated from Sub-Saharan countries and that their health status appeared to be directly linked to the poor and precarious living conditions in transit [13].…”
Section: A the Patient Population In Distress At Seamentioning
confidence: 99%
“…All the studies coincide in the scarce number of referrals to hospitals due to the reduced severity of the pathologies. According to Méndez‐Rodríguez, 2016, the musculoskeletal pathologies were the most predominant; whereas Ponce‐Blandón et al., 2020 concluded that the most common diagnosis in a study conducted in Almeria corresponds to dermatological pathologies. This coincides with the present study, where the most salient pathologies were the dermatological and the musculoskeletal ones, which might have occurred during the voyage or even be preexisting.…”
Section: Discussionmentioning
confidence: 99%
“…When contrasting the results of this analysis with other similar results, both differences and similarities are noticed. In the studies compared (Matos‐Castro & Padrón‐Peña, 2008; Méndez‐Rodríguez, 2016; Ponce‐Blandón et al., 2020; Trovato et al., 2016), immigrants from Africa and young men predominate. The reasons were related to attaining better quality of life and getting a job, objectives that were favored by the summer months and by the Mediterranean weather in all of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, almost 17,000 migrants have reached the coasts of the Canary Islands, six times more than the year before. People fleeing their home in Africa arrive to the Canary Islands after embarking on a long journey during which for many days they are exposed to extreme climatic conditions, violence, pulmonary toxic substances, hunger and thirst [2][3][4].…”
mentioning
confidence: 99%